Comparison of the Effect of Lecture and Group Discussion on Health Workers' Knowledge and Attitudes about Asthma Based on the IraPEN Program - Raziye Emambakhsh; Moghaddameh Mirzaee; Abedin Iranpour; Roghaieh Ershad Sarabi (Kerman University of Medical Sciences, 2022)
Background: The group discussion method is one of the student-centered and active teaching methods in which learners actively participate in educational activities using discussion, and they are given the opportunity to share their opinions and experiences with others.Objectives: The present study was conducted to compare the effects of the group discussion method and the lecture method on health workers' knowledge and attitudes.Methods: In this quasi-experimental study, 70 health workers working in Baft, Kerman province, were selected by census method and divided into two groups of 35 people. Asthma-related educational content was presented for one group as a lecture and the other as a group discussion. Before and after the intervention, health workers' knowledge and attitudes scores were evaluated and compared using a researcher-made questionnaire.Results: The mean age of participants was 38 ± 2.7 years. After the intervention, the mean score of attitude was 65.86 ± 6 in the lecture group and 68.66 ± 4.7 in the group discussion group, indicating a significant difference (p = 0.04). The mean score of knowledge after the intervention was 11.4 ± 1.66 in the lecture group and 11.28 ± 1.6 in the group discussion group, which was not statistically significant (p = 0.77). In both groups, the mean scores of knowledge and attitude increased significantly after the intervention (p<0.0001).Conclusion: The results showed that education affected the increase of health workers' knowledge and attitudes in both groups. Also, the group discussion method had a greater effect on increasing the attitude of individuals compared to the lecture method; however, this effect was not significant for knowledge. Therefore, it can be concluded that for the training of health workers, it is better to use integrated teaching methods to create deep and efficient learning as well as positive attitude and motivation.